Report on the Project for Establishment of the Standardized Korean Laboratory Terminology Database, 2015 - Jung, Bo Kyeung; Kim, Jeeyong; Cho, Chi Hyun; Kim, Ju Yeon; Nam, Myung-Hyun; Shin, Bong Kyung; Rho, Eun Youn; Kim, Sollip; Sung, Heungsup; Kim, Shinyoung; Ki, Chang-Seok; Park, Min Jung; et al. (Journal of Korean medical science, 2017)
The National Health Information Standards Committee was established in 2004 in Korea. The practical subcommittee for laboratory test terminology was placed in charge of standardizing laboratory medicine terminology in Korean. We aimed to establish a standardized Korean laboratory terminology database, Korea-Logical Observation Identifier Names and Codes (K-LOINC) based on former products sponsored by this committee. The primary product was revised based on the opinions of specialists. Next, we mapped the electronic data interchange (EDI) codes that were revised in 2014, to the corresponding K-LOINC. We established a database of synonyms, including the laboratory codes of three reference laboratories and four tertiary hospitals in Korea. Furthermore, we supplemented the clinical microbiology section of K-LOINC using an alternative mapping strategy. We investigated other systems that utilize laboratory codes in order to investigate the compatibility of K-LOINC with statistical standards for a number of tests. A total of 48,990 laboratory codes were adopted (21,539 new and 16,330 revised). All of the LOINC synonyms were translated into Korean, and 39,347 Korean synonyms were added. Moreover, 21,773 synonyms were added from reference laboratories and tertiary hospitals. Alternative strategies were established for mapping within the microbiology domain. When we applied these to a smaller hospital, the mapping rate was successfully increased. Finally, we confirmed K-LOINC compatibility with other statistical standards, including a newly proposed EDI code system. This project successfully established an up-to-date standardized Korean laboratory terminology database, as well as an updated EDI mapping to facilitate the introduction of standard terminology into institutions.